A CASE STUDY OF NL INFLUENCE IN UNIS FKIP ENGLISH DEPARTMENT STUDENTS' INTERLANGUAGE - Irmala Sukendra; Agus Mulyana; Imam Sudarmaji (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2018)
Regardless to the facts that English is being taught to Indonesian students starting from early age, many Indonesian thrive in learning English. They find it quite troublesome for some to acquire the language especially to the level of communicative competence. Although Krashen (1982:10) states that ???language acquirers are not usually aware of the fact that they are acquiring language, but are only aware of the fact that they are using the language for communication???, second language acquisition has several obstacles for learners to face and yet the successfulness of mastering the language never surmounts to the one of the native speakers. Learners have never been able to acquire the language as any native speakers do. Mistakes are made and inter-language is unavoidable. McNeili in Ellis (1985, p. 44) mentions that ???the mentalist views of L1 acquisition hypothesizes the process of acquisition consists of hypothesis-testing, by which means the grammar of the learner???s mother tongue is related to the principles of the ???universal grammar???.??? Thus this study intends to find out whether the students go through the phase of interlanguage in their attempt to acquire second language and whether their interlanguage forms similar system as postulated by linguists (Krashen).